The influence of COVID-19 on the practice of physical activity in the European Union countries - Diego Álvarez-Lourido; José Luis Paniza-Prados; Antonio Álvarez-Sousa (Gaceta Sanitaria)
Objective: Analyze how pandemics contribute to the increase in social inequalities in the health sector. Method: Data are taken from Eurobarometer 97.3. We use the Generalized Structural Equation Model (GSEM) methodology for this analysis. Results: People with lower socio-economic status, considered to be of lower social class, living in areas with worse infrastructure for practicing physical activity, and in countries with high levels of social inequality, are less likely to engage in leisure time physical activity. In addition, these individuals are more likely to interrupt physical activity practices as a result of COVID-19. In contrast, people of higher socio-economic status, considered to be of upper class, living in contexts where there are opportunities for physical activity, and in countries with low levels of social inequality, are more likely/ to belong to the group of those who increased the frequency of practicing physical activity in free time/ to have increased the frequency of their leisure time physical activity. Conclusions: There are widespread inequalities in leisure time physical activity linked to personal variables (social status and subjective social class) and contextual variables (infrastructures and Gini Index) that were significantly aggravated with the COVID-19 pandemic. Resumen: Objetivo: Investigar si esta tesis se cumple con la pandemia de COVID-19. Método: Los datos provienen del Eurobarómetro 97.3. Para este análisis se utilizó la metodología del Modelo de Ecuaciones Estructurales Generalizadas (GSEM). Resultados: Las personas con un nivel socioeconómico más bajo, consideradas de una clase social inferior, que viven en áreas con una infraestructura deficiente para la práctica de actividad física, y en países con altos niveles de desigualdad social, tienen menos probabilidades de participar en actividad física en su tiempo libre. Además, estas personas fueron más propensas a interrumpir la práctica de actividad física como resultado de la COVID-19. En contraste, las personas con un nivel socioeconómico más alto, consideradas de una clase social superior, que viven en contextos donde existen oportunidades para la actividad física y en países con bajos niveles de desigualdad social, tienen más probabilidades de haber aumentado la frecuencia de la práctica de actividad física en su tiempo libre o la frecuencia de actividad física en su tiempo de ocio. Conclusiones: Existen desigualdades generalizadas en la actividad física en el tiempo de ocio relacionadas con variables personales (estatus social y clase social subjetiva) y variables contextuales (infraestructuras e índice de Gini), que se agravaron significativamente con la pandemia de COVID-19.